2014
DOI: 10.4254/wjh.v6.i7.496
|View full text |Cite
|
Sign up to set email alerts
|

CEUS and Fibroscan in non-alcoholic fatty liver disease and non-alcoholic steatohepatitis

Abstract: < 0.001). The TTP in the PV was longer in both patient groups but reached statistical significance only in the NASH patients compared with the controls (NASH 79.5 ± 37.8 vs controls 43.2 ± 30, P < 0.01). In the LP, the Peak%, RBV and RBF were significantly reduced in the NAFLD and NASH patients compared with the controls (Peak%: NAFLD 43.2 ± 7.3, NASH 41.7 ± 7.7 vs controls 56.6 ± 6.3, P < 0.001; RBV: NAFLD 4851.5 ± 2009, NASH 5069.4 ± 2292.5 vs controls 6922.9 ± 2461.5, P < 0.05; RBF: NAFLD 55.7 ± 10.1, NA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 23 publications
3
9
0
1
Order By: Relevance
“…Besides fibrosis, multivariate analysis in our study also showed that inflammation was another independent factor related to the liver elasticity of NAFLD rabbits ( B = 1.248, 95% CI 0.519-1.977, P ≤ 0.001). This was consistent with that reported in previous studies [27, 28] and may be related to the inflammatory cell infiltration and increased pressure in the liver. However, our finding was different from those reported by Lee et al [15] and Kang et al [17].…”
Section: Discussionsupporting
confidence: 94%
“…Besides fibrosis, multivariate analysis in our study also showed that inflammation was another independent factor related to the liver elasticity of NAFLD rabbits ( B = 1.248, 95% CI 0.519-1.977, P ≤ 0.001). This was consistent with that reported in previous studies [27, 28] and may be related to the inflammatory cell infiltration and increased pressure in the liver. However, our finding was different from those reported by Lee et al [15] and Kang et al [17].…”
Section: Discussionsupporting
confidence: 94%
“…Lastly, CEUS imaging is sensitive to fatty liver disease progression and can accurately detect vascular features of NASH 20 . It was shown that the CEUS-based PE and WIR parameters decreased in fatty livers and consistent with previous studies 20 , 23 . Fat accumulation in the liver parenchyma can produce microvascular constriction and blood flow resistance during the pathologic progression of NAFLD disease.…”
Section: Discussionsupporting
confidence: 92%
“…If unhindered, hepatic vein transit time and intrahepatic circulatory time progressively decrease with liver disease severity due in part to arteriovenous shunting and a hyperdynamic circulatory state (i.e., temporal kinetic changes in MB contrast agent flow) 21 , 22 . In the case of NASH, this progressive blood flow derangement within the liver precedes liver fibrosis development 23 and any of the eventual complications of cirrhosis, such as HCC and portal vein thrombus 22 . It is worth noting that fibrotic changes also increase the absolute peak of contrast enhancement during CEUS imaging since arteriovenous shunts reduce the rate of MB dissolution as the contrast agent bypasses capillary beds 24 .…”
Section: Introductionmentioning
confidence: 99%
“…The result was similar to the previous studies on determining liver fat content by 1 H-MRS [21][22][23] . Most patients diagnosed with fatty liver have liver function damage and dyslipidemia.…”
Section: Correlation Analysis Between Metabolic Indices and Fat Contesupporting
confidence: 91%